(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
Exhumation is the retrieval of a previously buried body for post-mortem examination1. It involves disinterment of the body to investigate suspected homicide, to establish doubtful identity, or to answer claims for compensation, malpractice and the like2. Exhumation provides a lot of medico-legal information which is useful to investigating authorities as well as bereaved relatives, especially where there is dispute regarding identity of the person or doubt about the manner of death. The meticulous and careful medico-legal autopsy is useful in such cases even though exhumation is carried out after reasonable period.